2019
DOI: 10.1002/cam4.2099
|View full text |Cite
|
Sign up to set email alerts
|

Identification of competitive endogenous RNAs network in breast cancer

Abstract: Background MiRNAs can regulate gene expression directly or indirectly, and long noncoding RNAs as competing endogenous RNA (ceRNAs) can bind to miRNAs competitively and affect mRNA expression. The ceRNA network is still unclear in breast cancer. In this study, a ceRNA network was constructed, and new treatment and prognosis targets and biomarkers for breast cancer were explored. Methods A total of 1 096 cancer tissues and 112 adjacent normal tissues to cancer from the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The comparison results of Lv et al showed that all key genes were included in the upregulation group of tumor versus normal, while CDC25A, KIF18B, KIF2C, ORC1, RAD54L, and TPX2 were in the upregulation group of TNBC versus non-TNBC [ 19 ]. R package edgeR [ 18 ] was used to normalize and analyze the differential expression of mRNAs, lncRNAs, and miRNAs of BC in the research of Wang et al and Gao et al [ 20 , 21 ]. The result showed that all seven genes were upregulated in breast cancer tissues, which was consistent with our result.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparison results of Lv et al showed that all key genes were included in the upregulation group of tumor versus normal, while CDC25A, KIF18B, KIF2C, ORC1, RAD54L, and TPX2 were in the upregulation group of TNBC versus non-TNBC [ 19 ]. R package edgeR [ 18 ] was used to normalize and analyze the differential expression of mRNAs, lncRNAs, and miRNAs of BC in the research of Wang et al and Gao et al [ 20 , 21 ]. The result showed that all seven genes were upregulated in breast cancer tissues, which was consistent with our result.…”
Section: Resultsmentioning
confidence: 99%
“…Lv et al downloaded RNA-seq data of BC from TCGA database and applied the R package edgeR [ 18 ] for DEG analysis to explore the pathogenesis and prognosis of TNBC [ 19 ]. Moreover, we had collected other DEG consequences on BC versus normal tissues to further verify whether the expression trend of our key genes is correct [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, clarifying the underlying mechanism of CRC progression and identifying novel targets are of great importance. Circular RNAs (circRNAs) are characterized by their unique closed loop structure (Wang et al, 2019b;Ye et al, 2019). In recent years, accumulating studies have demonstrated that circRNAs are involved in the progression of various cancers, including ovarian and liver cancer Wu et al, 2019), and emerging evidence has shown that circRNAs can sponge miRNAs and interfere with their biological function and thus participate in carcinogenesis (Meng et al, 2017;Cui et al, 2018;Verduci et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen receptor signaling has also been shown to influence the expression of microtubule-associated protein tau ( MAPT ) such that the ER inhibitor fulvestrant can promote MAPT downregulation and thereby increase breast cancer cell sensitivity to taxane-based chemotherapy [ 41 ]. PP14571 , also referred to as AC110619.1 , is a long noncoding RNA that is capable of competitively binding microRNAs and thereby indirectly altering the expression of important genes associated with breast cancer progression [ 42 ].For in vitro experiments, paclitaxel- and adriamycin-resistant MCF-7/Tax cell lines were established using the chemosensitive MCF-7 parental cell line, and were used as chemoresistant breast cancer cell model systems with basic drug resistance characteristics. We also found that the expression of KDM7A was upregulated in chemoresistant cells (MCF-7/Adr and MCF-7/Tax), while MAPT and PP14571 were downregulated compared with the chemosensitive breast cancer control cell group (MCF-7/Con).…”
Section: Discussionmentioning
confidence: 99%